Efektivitas Peningkatan Kompetensi Pedagogik Melalui Workshop: Studi Terhadap Guru Pendidikan Agama Islam Sekolah Menengah Pertama Kabupaten Bintan - Dartoyo Radjikin (MGMP PAI SMP BINTAN, 2022)
This study aims to analyze the effectiveness of workshop activities in improving the pedagogic competence of GPAI SMP in Bintan Regency. The study lasted for six months in which participants provided documents in the form of learning tool reports. The results of the data analysis showed that Islamic religious education teachers experienced a positive increase in the competence of preparing lesson plans after attending the workshop compared to before participating in the activity. . Data sources include reflective teaching sessions conducted with field observations, teacher documents and lesson planning documents. Based on the results of this study, the authors recommend to PAI teachers at SMP in Bintan Regency to optimize their roles as planners, organizers, and assessors of learning, to school principals to facilitate PAI teachers to improve their pedagogical competencies so that it has an impact on improving the quality of education in schools, to the Education Office and The Office of the Ministry of Religion of Bintan Regency to always facilitate PAI MGMP activities by involving them in various trainings so that they can improve the quality of education in Bintan Regency in particular and in the Riau Islands Province in general.